2018
DOI: 10.1016/j.ymthe.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Radiation Conditioning Enables CAR T Cells to Mitigate Antigen Escape

Abstract: CD19 chimeric antigen receptors (CARs) have demonstrated great efficacy against a range of B cell malignancies. However, antigen escape and, more generally, heterogeneous antigen expression pose a challenge to applying CAR therapy to a wide range of cancers. We find that low-dose radiation sensitizes tumor cells to immune rejection by locally activated CAR T cells. In a model of pancreatic adenocarcinoma heterogeneously expressing sialyl Lewis-A (sLeA), we show that not only sLeA + but also sLeAtumor cells exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(156 citation statements)
references
References 43 publications
5
151
0
Order By: Relevance
“…For example, in preclinical glioblastoma and pancreatic tumor mouse models, the combination of radiation with CAR T cell therapy has proven to act synergistically. [53][54][55] In terms of successful implementation of such combined radioimmunotherapeutic approaches, the rise and induction of radioresistant tumor cells are a significant aspect that should be taken into consideration. Therefore, the major focus of this work was to analyze the effect of (Uni)CAR T cells on radioresistant HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in preclinical glioblastoma and pancreatic tumor mouse models, the combination of radiation with CAR T cell therapy has proven to act synergistically. [53][54][55] In terms of successful implementation of such combined radioimmunotherapeutic approaches, the rise and induction of radioresistant tumor cells are a significant aspect that should be taken into consideration. Therefore, the major focus of this work was to analyze the effect of (Uni)CAR T cells on radioresistant HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that radiation significantly induced the expression of NKG2D ligands on malignant cells, possibly explaining the synergy between the two methods described above. DeSelm and colleagues [202] further confirmed that low-dose radiation conditioning sensitizes tumor cells (not only sLeA + but also sLeA -) to CARsLeA T cells in a model of heterogeneous pancreatic adenocarcinoma.…”
Section: Combination With Radiotherapymentioning
confidence: 84%
“…While radiotherapy is rarely used in the treatment of ovarian cancer [37], recent evidence suggests that radiotherapy may be an effective preconditioning regimen for CAR T cell therapy [38]. In addition to promoting T cell infiltration into the tumour, radiation also upregulates the expression of cell death ligands such as Fas and TRAIL that induce T cell cytotoxicity against tumour cells [38,39].…”
Section: Discussionmentioning
confidence: 99%